1970
DOI: 10.4314/mmj.v27i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of chronic suppurative otitis media at Queen Elizabeth Central Hospital, Blantyre, Malawi: A cross-sectional descriptive study

Abstract: Background Chronic suppurative otitis media (CSOM) is still a significant health problem in developing countries. Therefore, it was pertinent to determine the local Malawian microbiology in order to guide adequate treatment, avoid complications, and provide records for future reference.Aim The study sought to determine the CSOM-causing microorganisms at Queen Elizabeth Central Hospital in Blantyre, Malawi, and establish their relationship signs and symptoms, and with the demographic pattern of the study.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
7
23
0
Order By: Relevance
“…The finding of this study regarding the P.aeruginosa predominance in CSOM was in agreement with local studies; Alsaimary, et al (19.4%)27Al-Hilli,201528, Aldhaher andHassan,2018(Aldhaher &Hassan, 2018;Arwa Hammodi Karim, 2005). Similarly, the finding of this study regarding the predominance of P.aeruginosa was also in agreement with other global studies (Chirwa et al, 2015;Madana et al, 2011;Rath, Das, & Padhy, 2017). The predominance of P.aeruginosa in CSOM can be accounted to their minimal nutritional requirement and potential ability to resist antibiotics (Pollock .M, 1996).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of this study regarding the P.aeruginosa predominance in CSOM was in agreement with local studies; Alsaimary, et al (19.4%)27Al-Hilli,201528, Aldhaher andHassan,2018(Aldhaher &Hassan, 2018;Arwa Hammodi Karim, 2005). Similarly, the finding of this study regarding the predominance of P.aeruginosa was also in agreement with other global studies (Chirwa et al, 2015;Madana et al, 2011;Rath, Das, & Padhy, 2017). The predominance of P.aeruginosa in CSOM can be accounted to their minimal nutritional requirement and potential ability to resist antibiotics (Pollock .M, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…H, et al,2013;Al-marzoqi, Hussein, Mohammad, Taee, & Yheea, 2013, who found that poly-microbial infection was higher than monomicrobial infection. In this regard results of the current study was in harmony with the well-known fact that microbial infection of the ear usually polymicrobial (Bakaletz, 2010;Mittal et al, 2015b). For precise identification of Pseudomonas spp to species level, lipoprotein L (OprL) gene was selected with specific primer designated by Vos et al, 1997, this primer showed great specificity to detect Pseudomonas to species level and it is applicable for routine detection of P. aeruginosa in clinical samples, has been used in several studies; Najafi et al, 2015b;Neamah & Department, 2017).…”
Section: Discussionsupporting
confidence: 85%
“… 11 We observed polymicrobial infections in 7.3% cases, which is a very common occurrence in CSOM and many studies have reported mixed pathogens including bacteria and fungus. 5 , 8 , 9 Polymicrobial growths may be well explained by the fact that the perforated ear drum facilitates coliforms such as E. coli , K. pneumoniae and P. aeruginosa to establish infection in wet and poor hygienic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota of CSOM include aerobes, anaerobes and fungi as potential pathogens though its reported profile and frequency differ based on patient’s age, geography and the presence of complications like cholesteatoma. 8 Frequently isolated aerobic bacteria include P. aeruginosa, S. aureus, E. coli, S. pyogenes, K. pneumoniae and Proteus spp. or mixed infections.…”
Section: Introductionmentioning
confidence: 99%
“…The ear swab culture done on our patients showed positivity in 47 patients out of 67 with an overall incidence rate of 70%, the results of the studies done by other authors also showed more or less a similar finding. 16,17 A study done in Pakistan by Aslam et al showed 76% of the swab samples showed growth in the culture report, another study in India done by Poorey et al showed growth in 82% of the samples and in most of the studies majority of the subjects showed mono-microbial growth and mixed growth was seen in less than 10% of the patients with CSOM. 15,18 A study done in Iran had showed 100% mono-microbial etiology in CSOM patients.…”
Section: Discussionmentioning
confidence: 99%